Alkene Difunctionalization Using Hypervalent Iodine Reagents: Progress and Developments in the Past Ten Years - Ji Hoon Lee; Sungwook Choi; Ki Bum Hong (Molecules, 2019)
Hypervalent iodine reagents are of considerable relevance in organic chemistry as they can provide a complementary reaction strategy to the use of traditional transition metal chemistry. Over the past two decades, there have been an increasing number of applications including stoichiometric oxidation and catalytic asymmetric variations. This review outlines the main advances in the past 10 years in regard to alkene heterofunctionalization chemistry using achiral and chiral hypervalent iodine reagents and catalysts.